Cellulose nanocrystals to modulate the self-assembly of graphene oxide in suspension - Vikram Singh Raghuwanshi; Swambabu Varanasi; Warren Batchelor; Gil Garnier (Materials & Design, 2022)
Controlling the self-assembly(SA) of cellulose nanocrystals(CNC) and graphene-oxide(GO) sheets at nanoscale is crucial for exploiting properties of both CNC and GO. The SA mechanism of GO, CNC and CNC/GO in suspension is evaluated at different concentrations and mixing ratios. SAXS determine the interparticle distance, interaction and distribution of CNC and GO to resolve the self-assembling mechanism. At lower concentrations, the GO sheets are distributed randomly and separated by a large inter-sheet distance of 83 nm with poor inter-sheet interaction. As increases the GO concentration, the inter-sheet repulsion results in a nematic arrangement with the inter-sheet distance decreasing from 83 to 52 nm. Mixing isotropic and nematic phase of CNC with GO at different CNC/GO ratio from 2 to 50 shows transitions from isotropic, to biphasic and nematic state. In isotropic state, at low CNC/GO ratio, the GO sheets are randomly distributed between the CNC rods which increases the CNC inter-rod distance from 22 to 51 nm. However, at higher CNC/GO ratios, steric repulsion from the large amount of CNC forces the GO sheets to align following the direction of CNC nematic assembly. Understanding SA mechanisms of nanostructures in CNC-GO hybrid will enable to engineer applications for sensor, electronics and diagnostics.